Il vaso e i cocci. Note in margine a La llegenda del llibreter assassí de Barcelona. - DE CRISTOFARO, FRANCESCO (Scripta, 2013)
This essay seeks to investigate tangentially some questions regarding La llegenda del llibreter assassí de Barcelona: after having analyzed the approaches, methods and strategies -that Alberto Varvaro has thoroughly examined in the essay on Baroness di Carini's story-, and the literary quality achieved by Ramon Miquel i Planas in his work; and after having probed the paraliterary line of the so-called "famous trials" -mostly focusing on the naturalistic estrangement effect produced by literature works related to legal cases (e.g. the conventional diptych in Galdós's Realidad-Incógnita)-, the centre of attention shifts on the cultural, historical aspects of the bizarre relationship between kleptomania and bibliomania (especially in Flaubert). The article concludes with a swift overview of literary plagiarisms committed by Nodier, the presumed culprit of the forgery, from which the genealogy investigated by Miquel i Planas builds up: a culprit that, while committing several literary crimes, decides to write a jurisprudential treaty in order to systematize and sentence them.